2004
DOI: 10.1007/s00213-003-1633-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fear potentiated startle in rats following peripheral administration of secretin

Abstract: This investigation provides additional evidence that systemically administered secretin can influence a neural network implicated in the acquisition and expression of emotional behaviors, including fear and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…To our knowledge only one other neuropeptide or neuropeptide-mimetic, has been shown to block FPS. In this regard, Myers et al (2004) reported that secretin, a neurohormone neuropeptide, reduced FPS after systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge only one other neuropeptide or neuropeptide-mimetic, has been shown to block FPS. In this regard, Myers et al (2004) reported that secretin, a neurohormone neuropeptide, reduced FPS after systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm is therefore used as an important laboratory model of anxiety, both in animals [301, 369, 408, 498] and humans [11, 144, 147, 210]. The LC may contribute to the activation of the startle pathway in the fear-potentiated startle paradigm in two ways.…”
Section: Physiological Manipulation Of Locus Coeruleus Activitymentioning
confidence: 99%
“…This observation opens the way to consider retrograde vagus nerve stimulation as a possible indication for AD, and indeed preliminary reports indicate that this procedure may have beneficial effects on cognitive functions in patients suffering from AD [285, 414]. The electrical stimulation of the left vagus nerve is well established as a therapeutic procedure both in epilepsy [149] and treatment-resistant depression [301]. Interestingly, it has been shown that vagus nerve stimulation leads to increases in the firing rates of noradrenergic neurones in the LC and serotonergic neurones in the dorsal raphe nucleus [103].…”
Section: Pathological Alterations Of Locus Coeruleus Activitymentioning
confidence: 99%
“…Intravenous (IV) administration of secretin at a clinical dose was shown to pass through Blood-BrainBarrier [4] and that the peptide was transported into the brain by non-saturable transmembrane diffusion [2,4]. Besides, it was also shown that peripheral, IV, or intraperitoneal (IP) administered secretin could lead to i) c-fos expression changes in discrete brain regions, including NTS [128] and the central nucleus of amygdala [136]; ii) re-establishment of the communicative and affiliative interactions in autistic children [118]; and iii) modulation of neural networks in the acquisition and expression of emotional behaviors, including fear and anxiety [137]. Collectively, it is possible that endogenously synthesized secretin, either in the CNS or from peripheral endocrine tissues, acts in the neuronal network within prosencephalon, mesencephalon, and rhombencephalon to exert its central actions.…”
Section: Secretinmentioning
confidence: 99%